(untitled) (Research, Society and Development, 2021)
Objective: to reflect and characterize the main public policies and health programs and their impacts on growth and development in very early childhood. Method: This is a critical review arising from the study and debates on health policies aimed at very early childhood. Results and Discussion: By making a historical outline of public health policies in very early childhood, we can highlight advances in various aspects, whether in the creation, expansion or improvement of policies and approaches. Conclusion: It is evident the concern and attempts to offer policies aimed at the very early childhood with a view to adequate growth and development, although the risk and vulnerability situation of Brazilian children is in full compliance with social, economic and access to services inequalities, making it difficult to implementation since the legal framework and making it insufficient.